Biosurfactants from Waste: Structures and Interfacial Properties of Sophorolipids Produced from a Residual Oil Cake. Issue 2 (18th November 2019) - Jiménez‐Peñalver, Pedro; Koh, Amanda; Gross, Richard; Gea, Teresa; Font, Xavier
Abstract: Sophorolipids (SL) are microbial biosurfactants that have entered the market as detergent and cosmetic formulation ingredients. Current research is focused on the use of wastes to decrease the final production costs of SL and the environmental impacts. SL from wastes will help to move toward the circular economy only if the SL produced this way are pure enough and as efficient as current commercial SL. This manuscript focuses on the study of the structures and the interfacial properties of a crude SL natural mixture produced by solid‐state fermentation from a residual sunflower oil cake from the oil‐refining industry. Liquid chromatography–mass spectrometry (LC–MS) demonstrated that the diacetylated lactonic 18:1 SL was the most abundant SL of the mixture, followed by the correspondent acidic form. The surface tension‐lowering capacity was studied in a water–air interface at temperatures ranging from 15 to 50 °C. The minimum surface tension and critical micelle concentration were determined. The emulsion properties were similar to those obtained for the commercial nonionic surfactant Triton X‐100. The efficiency of the SL natural mixture was also proven successful for the displacement of a diesel slick. These results confirmed the effectiveness of SL produced from a real waste. Abstract :